Controlled Functionalization Strategy of Proteins Preserves their Structural Integrity While Binding to Nanocarriers - Ana Mateos‐Maroto; Meiyu Gai; Maximilian Brückner; Volker Mailänder; Svenja Morsbach; Katharina Landfester (Advanced Materials Interfaces)
Abstract The use of proteins as targeting agents often requires their chemical modification for their efficient attachment to a given surface. However, no control over the protein integrity and functionality has been demonstrated to date. Chemical over‐modification causes the loss of the native structure of the protein and thus limits its targeting efficiency. To preserve structural integrity, a minimal modification strategy of proteins is developed while maintaining their functionality. Apolipoprotein A1 (ApoA1) and liposomes are utilized as a nanocarrier platform. Monitoring NHS ester chemistry by time‐of‐flight mass spectrometry experiments, the proposed functionalization route allows the effective chemical coupling of the minimally modified ApoA1 to the surface of the liposomes via a click chemistry reaction. The stability of the modified ApoA1 is ensured by analyzing the secondary structure by circular dichroism spectroscopy and the corresponding melting point by nano differential scanning fluorimetry. Furthermore, ApoA1 attachment to the liposomes is confirmed by flow cytometry experiments. The procedure presented in this study has the potential to be easily transferred to other proteins while introducing only minimally necessary chemical modifications to be covalently attached to different drug delivery platforms. This can help to improve their targeting efficiency for future biomedical applications.